(untitled) (Texas Journal of Multidisciplinary Studies, 2023)
This article provides information on the history of television and radio in Karakalpakstan. The concept of television was the work of many individuals in the late 19th and early 20th centuries, with its roots initially starting from back even in the 18th century. The first practical transmissions of moving images over a radio system used mechanical rotating perforated disks to scan a scene into a time-varying signal that could be reconstructed at a receiver back into an approximation of the original image. Development of television was interrupted by the Second World War. After the end of the war, all-electronic methods of scanning and displaying images became standard. Several different standards for addition of color to transmitted images were developed with different regions using technically incompatible signal standards. Television broadcasting expanded rapidly after World War II, becoming an important mass medium for advertising, propaganda, and entertainment.